PENGEMBANGAN PENDIDIKAN MULTIKULTURAL BERBASIS KEARIFAN BUDAYA LOKAL PADA PERGURUAN TINGGI - Waway Qodratullah S. (Universitas Negeri Medan, 2016)
This paper discusses the idea of the multicultural education development strategy based on the local wisdom at higher education. Indonesia, as the largest archipelago in the world, certainly has diverse cultural base. The fact that ethnic and cultural plurality is not only justified historically, sociologically, and anthropologically, but also theologically. An important thing in the sustainability of the multicultural education is the loss of fanaticism and exclusivism tendencies.Therefore, the management of the proper local culture should become the core in the development of national education. The matter becomes the basis that the multicultural education suits to be the basis of the character education in higher education. Nevertheless, multicultural education does not mean eliminating the primordial identity because it will cause the social and cultural backwards. The Indonesian culture might not be narrowed down into particular ethnic and religion for such actions would not produce the original identity. Even worse, it will disappear the original identity. The development of the multicultural education based on the local culture is carried through some steps: Identifying and constructing the data base of local culture; Inserting the values of local wisdom into the core curriculum of higher education through the content of the Character Education Course; Using the contextual-holistic approach; Providing facilities and infrastructure in accommodating the form of local culture; Exploring the values of local wisdom in classrooms; Building and promoting the foundation of the character educators; and Evaluating the achievement of learning outcomesKata Kunci: Pendidikan, Multikultur, Kearifan Lokal, Pendidikan Tinggi